Adherence to a Mediterranean diet is associated with a better health-related quality of life: a possible role of high dietary antioxidant content - Bonaccio, Marialaura (BMJ Publishing Group, 2013)
OBJECTIVES: Mediterranean diet (MD) is associated with a reduced risk of major chronic disease. Health-related quality of life (HRQL) is a valid predictor of mortality. The aim of this study is to investigate the association between MD and HRQL and to examine the possible role of dietary antioxidants, fibre content and/or fatty acid components. DESIGN: Cross-sectional study on a sample of Italian participants enrolled in the Moli-sani Project, a population-based cohort study. Food intake was recorded by the Italian European prospective investigation into cancer and nutrition study food frequency questionnaire. Adherence to MD was appraised by a Greek Mediterranean diet score (MDS), an Italian Mediterranean diet index (IMI) and by principal component analysis (PCA). HRQL was assessed by the 36-Item Short Form Health Survey. SETTING: Molise region, Italy. PARTICIPANTS: 16 937 participants of 24 325 Italian citizens (age≥35). MAIN OUTCOMES: Dietary patterns and HRQL. RESULTS: Mental health was associated consistently and positively with MDS, IMI and an ‘Olive oil and vegetable’ pattern (PCA1), but negatively with an ‘Eggs and sweets’ pattern (PCA3). Physical health was associated positively with MDS and PCA1, but negatively with a ‘Meat and pasta’ pattern. Subjects with the highest MD adherence had 42% (MDS), 34% (IMI) or 59% (PCA1) statistically significant multivariable odds of being in the uppermost level of mental health, as compared with subjects in the lowest category. The associations disappeared after further adjustment for either total food antioxidant content or dietary fibre, while they were not modified by the inclusion of either monounsaturated or polyunsaturated fatty acids. Individuals in the highest PCA1 or PCA3 had significantly higher odds of being in the top level of physical health. CONCLUSIONS: Adherence to an MD pattern is associated with better HRQL. The association is stronger with mental health than with physical health. Dietary total antioxidant and fibre content independently explain this relationship.